Pandemic impact on girls in sport (Canadian Women; Sport and E-Alliance, 2021)
COVID-19 has profoundly impacted society, an impact that we will feel for years to come. Within sport, COVID-19 has resulted in huge revenue losses and deep cuts to programming. Every individual involved in sport, from leaders to athletes to coaches, at all levels of sport, felt these changes. But, the impact of those changes were likely not be experienced equally by all. Reviewing sport participation statistics from before COVID-19, fewer girls participated in sport compared to boys and girls experienced unique barriers to sport. The Pandemic Impact on Girls in Sport report, which collected data from over 5,000 Canadian families, shows that 1 in 4 girls are not committed to returning to sport. If we don`t act now to counter this trend, we might realize a new normal of over 350,000 girls sitting on the sidelines in the post-COVID-19 world. The success of sport in Canada will depend on girls` engagements and contributions; so now is the time to rethink how we can rebuild sport with and for them. As sport poises to return, there is an opportunity to change the minds of girls to commit to return. We must pay attention to what girls want. We must design with their needs at the centre. The time for action is now.